A new species of Aphelocheirus (Hemiptera: Heteroptera: Aphelocheiridae) from Morocco - Millán, Andrés; L'mohdi, Ouassima; Antonio Carbonell, José; Taybi, Abdelkhaleq Fouzi; Dakki, Mohamed (Zootaxa, 2016)
This paper provides the description of a new species of Aphelocheirus (Hemiptera: Heteroptera: Aphelocheiridae), Aphelocheirus pemae sp. nov. from Morocco. The species was found in two sites located in different basins (Sebou and Moulouya rivers) that are separated by approximately 400 km. Photographs of the dorsal habitus of the female and illustrations of the male genitalic structures are provided. A graphical key to species of the genus in Western Europe and the Maghreb is also included. The new species can be easily distinguished by the unique shape of the left and right parameres and absence of apical spines on the aedeagus.